Protein expressions of PDKL, XIAP, S6K1, MEK1/2 and ERK1/2 which function in growth, differentiation and survival of non-vitrified and vitrified murine preimplantation embryos / Mohd Fazirul Mustafa - Mustafa, Mohd Fazirul (2016)
Embryo development is closely related to the proteins which are differentially expressed in each developmental stage. Proteins are crucial in regulating biological processes such as growth development, migration, proliferation, differentiation, and survivability of preimplantation embryos. Therefore, the objectives of this study are to analyse the expression of PDK1, XIAP, S6K1, MEK1/2 and ERK1/2 proteins at the 2- cell and blastocyst stages and investigate the effect of vitrification on the expression of these proteins. Murine oocytes were superovulated with 10 i.u PMSG, followed 48 hours later with 10 i.u hCG. Vitrification of the embryos at the blastocyst stage was carried out using ESF40 as a cryoprotectant. Proteins expression was observed by Western blot analysis. Experiments were carried out in triplicates. Results showed that five selected proteins; PDK1, XIAP, S6K1, MEK1/2 and ERK1/2 were predominantly expressed in embryo cytoplasm and exhibited notable involvement of PI3K and MAPK at the 2-cell stage. Vitrified blastocysts showed a decrease in the expression of ERK1/2, S6K1 and XIAP compared to non-vitrified blastocyst. This study showed that the expression of these proteins in embryos was developmental stage dependent. Each stage of development is responsible for specific biological processes in cell growth. Vitrification was shown to modulate the protein expression involved in embryonic developmental competence, associated with the activation of the apoptotic pathway through regulation of the expressions of PDK1, XIAP, S6K1, MEKl/2 and ERKl/2.